2012
DOI: 10.1603/ec11425
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation by Western Corn Rootworm (Coleoptera: Chrysomelidae) to Bt Maize: Inheritance, Fitness Costs, and Feeding Preference

Abstract: We examined inheritance of resistance, feeding behavior, and fitness costs for a laboratory-selected strain of western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), with resistance to maize (Zea maize L.) producing the Bacillus thuringiensisBerliner (Bt) toxin Cry3Bb1. The resistant strain developed faster and had increased survival on Bt maize relative to a susceptible strain. Results from reciprocal crosses of the resistant and susceptible strains indicated that inheritan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 73 publications
5
58
0
Order By: Relevance
“…However, increased mortality of western corn rootworm larvae caused by entomopathogens was detected in six of the eight experiments conducted in this study (Table 3). These results parallel the work of Petzold-Maxwell et al (2012a), which also found that entomopathogens did not increase Þtness costs of resistance to Cry3Bb1 maize for western corn rootworm. Although signiÞcantly higher mortality was observed for the susceptible strain compared with resistant strain at some concentration of conidia in the seedling mat assay with B. bassiana, mortality in this assay was highly variable and did not differ signiÞcantly from zero ( Fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, increased mortality of western corn rootworm larvae caused by entomopathogens was detected in six of the eight experiments conducted in this study (Table 3). These results parallel the work of Petzold-Maxwell et al (2012a), which also found that entomopathogens did not increase Þtness costs of resistance to Cry3Bb1 maize for western corn rootworm. Although signiÞcantly higher mortality was observed for the susceptible strain compared with resistant strain at some concentration of conidia in the seedling mat assay with B. bassiana, mortality in this assay was highly variable and did not differ signiÞcantly from zero ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Both the results of this study and the results of Petzold-Maxwell et al (2012a), found an absence of Þtness costs in the presence of entomopathogens. In a study of Þve Cry3Bb1-resistant western corn rootworm strains (including the strain used here), Oswald et al (2012) did not detect Þtness costs for survival, fecundity, and egg viability, but did detect increased Þtness for resistant strains through faster developmental rate and higher fecundity.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…For example, Bt-resistant strains of P. xylostella had reduced survival and fecundity in one study (Groeters et al 1994), but no Þtness costs of resistance in other studies (Tang et al 1997, Ramachandran et al 1998. For the western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), an important pest of maize, no Þtness costs of Bt resistance were shown for a Cry3Bb1-resistant, nondiapausing strain in a study by Oswald et al (2012) and Petzold-Maxwell et al (2012); however, Meihls et al (2012) found evidence of Þtness costs. Gassmann et al (2009) found that the likelihood of a study detecting Þtness costs was positively correlated with the number of lifehistory characteristics measured.…”
Section: Discussionmentioning
confidence: 97%
“…While all cases of resistance to Bt cotton isolated in Australia have been recessive, at least two reported cases of practical resistance outside of Australia were partially dominant (reviewed in [6]; see also [23,24]). Therefore, concurrent with a shift in strategy, is a recognition that the highest priority in terms of novel resistance is detecting dominant resistance alleles.…”
mentioning
confidence: 99%